The capacity for monitoring & evaluation systems in the North West provincial government departments - Mataka, Themba (My University, 2016)
The South African government has extended the constitutional mandate of the Auditor-general to cater specifically for performance information in the public sector, which has resulted in the rollout of a Government-wide Monitoring and Evaluation system designed to enhance efficiency, accountability and transparency in the public sector. This study investigated the capacity gaps and systems problems in the M&E systems that caused a majority of the North West provincial government departments to receive qualified opinion on performance information between 2010/11 and 2013/14 financial years. A qualitative approach was used, supported by interviews and documentary analysis to extract rich data. The capacity gaps and systems problems in the M&E systems in the provincial departments manifested themselves in the form of inadequate oversight role; poor leadership; malicious compliance; lack of approved M&E policies; lack of uniformity in M&E structure and location; lack of M&E skills, inadequate budget; lack of accountability and transparency. The overall conclusion of the study is that adequate oversight role and effective leadership, and political stability are central in the implementation process of M&E systems. Key recommendations of the study include amongst others capacitating the institutional oversight structures and leadership; approved M&E policies; streamline M&E systems; all programme managers should account for the M&E function; M&E systems should be fully resourced; and capacitate the M&E fora.
A Thesis submitted to the Graduate School of Public and Development Management in fulfilment of 50 percent of the requirement for the degree of Master of Management in Public Policy University of Witwatersrand, Johannesburg March 2015
Keywords: Public administration--South Africa--Management; Performance standards--South Africa--Evlauation; Civil service reform--South Africa